Legal Construction Appropriate Form of Business Agencies in The Development of Village-Owned Business Units By Notary Based on Law Number 6 of 2014 Concerning Village - Fandili Indrayana (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2022)
The legal construction of the Village Owned Enterprise Deed in choosing a business form sometimes becomes a problem. This research is aimed at the legal construction of the proper form of business entity in the Deed of Village-Owned Enterprises by a Notary based on Law Number 6 of 2014 concerning Villages. In addition, it is also to analyze the legal relationship of Village-Owned Enterprises as business entities in forming other legal entities as business activities using normative research methods. The results of the study state that, BUMDes is a village-owned enterprise established on the basis of the needs and potential of the village as an effort to improve community welfare with a family spirit, so the legal construction of the right form of business entity in the Deed of Village-Owned Enterprises by Notaries based on Law Law Number 6 of 2014 concerning Villages is a cooperative or PT (Persero). The relationship between Village-Owned Enterprises as a business entity and other legal entities as business units is basically a two-sided legal relationship (tweezijdige rechtsbetrekkingen), namely the legal relationship between two parties accompanied by the rights and obligations of both parties. We recommend that the Regulation of the Minister of Villages, Development of Disadvantaged Areas, and Transmigration Number 4 of 2015 concerning Establishment, Management and Management, and Dismissal of Village-Owned Enterprises does not limit the selection of legal construction of BUMDes business units, apart from that it is necessary to regulate BUMDes in the form of Laws especially regarding provisions state finances as separated capital, and the accountability of the board of directors.Keywords: Legal Construction, Village-Owned Business Unit Deed, Notary